Adaptation and validation of the Indonesia version social media engagement scale for adolescent - Ratri Pratiwi; Ainurizan Ridho Rahmatulloh; Rahimmatussalisa (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
The rise of social media has reshaped how people, especially adolescents, communicate and express themselves. Accurate assessment of social media engagement quality is critical for understanding its psychological, social, and behavioral effects, highlighting the need for psychometrically sound measurement tools. This study aims to adapt and test the psychometric properties of the Indonesian version of the SMEA scale. The study involved 851 participants aged 12–21 years. Content validity was assessed using Aiken’s V index based on ratings from 25 expert judges. Construct validity was evaluated through Confirmatory Factor Analysis (CFA), and reliability was tested using Cronbach’s alpha. Results showed Aiken’s V values ranged from 0.67 to 0.91, indicating good content validity. CFA supported the model’s goodness of fit, confirming construct validity. The instrument demonstrated high internal consistency, with a Cronbach’s alpha of 0.83. These findings indicate that the Indonesian version of the SMEA is a valid and reliable tool for assessing adolescents' social media engagement. Its application can support evidence-based interventions to foster healthy social media use and digital literacy.